Minat Pencarian Masyarakat Terhadap Intervensi Stunting Sebagai Upaya Penurunan Kejadian Stunting di Indonesia Selama Periode 2018-2022: Analisis Google Trends: Minat Pencarian Masyarakat terhadap Intervensi Stunting Sebagai Upaya Penurunan Kejadian Stunting di Indonesia Selama Periode 2018-2022: Analisis Google Trends - Prameswari, Najla Aurora; Prawesti, Magdalena Sabda; Astuti, Sukma Dewi; Yapita, Jennifer; Helmyati, Siti; Rosilia, Gifani; Aristyarini, Mitha; Sitorus, Nova Lidia; Pratiwi, Dessy (Amerta Nutrition, 2023)
Background: In 2018, the prevalence of stunting in Indonesia was 30.8%, which has led to renewed focus on targeted interventions. Although specific measures such as exclusive breastfeeding, complementary feeding, and immunization have been prioritized, achieving optimal coverage remains a challenge. Limited knowledge has been identified as a potential barrier to the interventions. This study acknowledges the effectiveness of internet platforms in providing stunting prevention information.  Objectives: To analyze search interest trends for exclusive breastfeeding, complementary feeding, and immunization from 2018 to 2022 using Google Trends. Methods: Google Trends was used to analyze search trends for the keywords 'exclusive breastfeeding', 'complementary feeding', and 'immunization' in Indonesia and three provinces with the highest number of searches, namely Central Sulawesi, East Nusa Tenggara, Southeast Sulawesi, Yogyakarta, Central Java, Bangka Belitung, and Bengkulu. The data were compared with the prevalence of stunting and coverage of interventions.   Discussion: Searches for exclusive breastfeeding tended to be stable, while searches for complementary feeding and immunization tended to spike at certain times. Analysis of the provinces with the highest number of searches showed that the high search volume did not necessarily correspond to the trends in the performance of interventions in the regions. Conclusions: Searches for 'exclusive breastfeeding', 'complementary feeding', and 'immunization' from 2018 to 2022 showed different trends. It's impossible to compare the data with the prevalence of stunting because of different trends. However, the data on search interest can illustrate community perceptions and practices around these interventions.